Investigaciones en torno a la identificación de hitos: recorridos con actores rurbanos y aplicaciones futuras en organizaciones sociales - Kenbel, Claudia Alejandra (2018)
This work aims to share research experiences in the perspective of communication and social development, particularly in what we have called the rurban problem. This is an idea that invites us to understand the survival experiences of thousands of family groups that, throughout the continent, work with elements, knowledge and rural practices in urban settings. Their presence stresses the dominant conceptions about what the idea of city is or should be. To address these experiences we develop a methodological strategy based on confl icting milestones as events that reveal to the public sphere tensions of senses between the modern urban and alternative conceptions. Specifically, the milestones can be identified from public policies that aff ect the social groups of interest.